Use of technologies in the people management area of organizations - Cristine Cavacini , Débora; Teresinha Agnolin , Cristiane; Cristina Groto, Luana; Barato Vanz , Eduarda (Seven Editora, 2023)
This article sought to identify the principal technologies used to develop processes in the People Management sectors in Brazilian companies. In addition, it was developed aware of the digital platforms implemented in companies, understanding how they contribute to the flow of processes, analyzing which have been the main benefits of being implemented, and finally, realizing which have been the main harms of their implementations. The study consisted of research whose approach is classified as explanatory. The research ranks concerning the focus on qualitative. Regarding the procedures, bibliographical research was used, which consists of explaining issues already published. The research took place on the most requested academic platforms such as Google Academic, Scielo, and Pepsico. It was possible to observe that the literature does not present much data on the subject; however, it is clear that technological innovation contributes to the improvement of people management processes in organizations. DOI: 10.56238/pacfdnsv1-068